The Punished Self, the Unknown Self, and the Harmed Self – Toward a More Nuanced Understanding of Self-Harm Among Adolescent Girls - Stänicke, Line Indrevoll (Frontiers in Psychology, 2021)
Self-harm among adolescents, mostly girls, has increased in the last years. Self-harm is associated with mental illness and the risk of suicide. This qualitative study aims to explore the lived experience of self-harm as it is related to everyday life and challenges among adolescents. Nineteen girls (13-18 years of age) in a clinical population (strategic selection) participated in personal interviews analyzed by Interpretative Phenomenological Analysis to capture how they made meaning of self-harm and essential features of experiencing self-harm. Adult persons with the first-hand experience of self-harm were included in the research analysis. Data-analysis resulted in three superordinate themes which all speak about ways to handle inner pain and vulnerability: 1. “I deserve pain”, 2. “I don’t want to feel anything”, and 3. “I’m harmed, and no one cares”. Each superordinate theme included four main themes characterizing essential features of difficult experiences during self-harm, the purpose of the action, self-descriptions, and the role of others during self-harm. The three superordinate themes are discussed as emerging self-representations – “the punished self”, “the unknown self” and “the harmed self” – during the transitional age of adolescence. This article argues that subjective personal data on self-harm related to adolescents’ everyday lives may indicate diversity in the capacity to integrate difficult needs, feelings, and traumatic experiences as part of the self. This knowledge may bring a nuanced understanding of self-harm in adolescence, enhance self-understanding and treatment motivation, and inform clinical adjustment.